Digital Innovation in Public Fund Management for Public Housing Finance: A Systematic Review Towards Smart Governance and Its Implications in DKI Jakarta - Asmianur, Refa; Oman Rohman Rakinda; Fahd Pahdepie; Mawar; Azhari Aziz Samudra (PT Inovasi Pratama Internasional, 2026)
This study examines digital innovation in public fund management for affordable housing financing through a Systematic Literature Review (SLR) approach, aiming to explore its contribution to the realization of smart governance. The review synthesizes relevant studies on digital governance, public financial management, and housing policy to identify patterns, challenges, and research gaps. The findings indicate that digital innovation—such as e-budgeting, integrated financial systems, and data-driven governance—has significantly improved administrative efficiency, transparency, and accountability in public finance. However, its impact on affordable housing financing remains limited due to fragmented institutional coordination, insufficient data integration, and weak organizational capacity. The study reveals that digital transformation often remains at a procedural level and fails to produce substantive governance improvements. Addressing this limitation, the study proposes an integrative framework in which smart governance is achieved through the alignment of three key dimensions: digital infrastructure, institutional capacity, and collaborative governance processes. This framework highlights that technological advancement alone is insufficient without organizational readiness and cross-sector coordination. The findings offer theoretical contributions to Public Administration by integrating digital governance and public financial management within the housing sector. Practically, the study provides policy implications relevant to urban contexts, including DKI Jakarta, in enhancing effective and data-driven housing finance governance.